2020
DOI: 10.1111/nmo.13793
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle score and irritable bowel syndrome: A cross‐sectional study in adults

Abstract: Background: Lifestyle modifications play an important role in the management of irritable bowel syndrome (IBS), but there is limited information on any associations of combined lifestyle-related factors with IBS in Middle Eastern populations. We, therefore, assessed the associations of a "lifestyle score," in analogy to lifestyle scores applied in studies of other disorders, with IBS in adults. Methods:In a cross-sectional study on 3363 Iranian adults, a healthy lifestyle score (HLS) was constructed using info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…22 Regarding dietary habits, this study showed significant differences in time spent eating, picky eating habits and having irregular meals between the IBS group and the non-IBS group, which is in agreement with the findings of Hajishafiee et al, who showed subjects with IBS had irregular meal patterns, fast eating rates, and high intakes of fatty and spicy foods and caffeinated beverages and consumed fewer fruits and vegetables than healthy people. 23 This study showed statistically significant differences between both groups with regard to depression (p<0.05). Mild, moderate and severe depression were reported in 60.0%, 14.3% and 25.7% of patients with IBS, whereas most (82.9%) of the non-IBS participants reported mild depression.…”
Section: Main Findingsmentioning
confidence: 54%
See 1 more Smart Citation
“…22 Regarding dietary habits, this study showed significant differences in time spent eating, picky eating habits and having irregular meals between the IBS group and the non-IBS group, which is in agreement with the findings of Hajishafiee et al, who showed subjects with IBS had irregular meal patterns, fast eating rates, and high intakes of fatty and spicy foods and caffeinated beverages and consumed fewer fruits and vegetables than healthy people. 23 This study showed statistically significant differences between both groups with regard to depression (p<0.05). Mild, moderate and severe depression were reported in 60.0%, 14.3% and 25.7% of patients with IBS, whereas most (82.9%) of the non-IBS participants reported mild depression.…”
Section: Main Findingsmentioning
confidence: 54%
“… 22 Regarding dietary habits, this study showed significant differences in time spent eating, picky eating habits and having irregular meals between the IBS group and the non-IBS group, which is in agreement with the findings of Hajishafiee et al, who showed subjects with IBS had irregular meal patterns, fast eating rates, and high intakes of fatty and spicy foods and caffeinated beverages and consumed fewer fruits and vegetables than healthy people. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have reported that healthy lifestyle score was related to mortality, diabetes, and cardiovascular diseases [39-41]. In addition, we have previously reported the relationship between healthy lifestyle score and depression, anxiety, and irritable bowel syndrome [42, 43].…”
Section: Discussionmentioning
confidence: 87%
“…For instance, a healthy lifestyle comprises exercising, controlling diet, modifying bedtime habits, controlling weight, and regular eating of fruits and vegetables among others [50]. The surfacing of e-health technologies provides extremely reachable and low-cost information to encourage healthy habits among patients [51]. Since many countries have developed numerous e-health intervention programs to aid citizens to avoid unhealthy behavior such as smoking and intervention programs to monitor and treat various pandemic such as COVID 19.…”
Section: Healthy Lifestylementioning
confidence: 99%